A note on the behind armour effects from perforated alumina/aluminium targets - Hazell, Paul J.; Fellows, Neil A.; Hetherington, John G. (Elsevier, 1998)
A thin, ceramic-faced armour, separated from a thick metal block, has been subjected to high-velocity impact by a 6.35 mm diameter steel sphere. Experimental work was carried out which compared firings into ceramic-faced aluminium armour, separated from thick aluminium witness blocks, with firings into the thick aluminium blocks alone. The depth of penetration and the area of damage were measured and an estimated percentage weight saving due to the inclusion of the ceramic-faced armour was calculated at varying velocity. This note yields useful information for the design and application of ceramic applique systems.
Keywords: impact; ceramic-faced armour; behind armour debris; hypervelocity